Quadrulella texcalense sp. nov. from a Mexican desert: An unexpected new environment for hyalospheniid testate amoebae - Pérez-Juárez, Horacio; Serrano-Vázquez, Angélica; Kosakyan, Anush; Mitchell, Edward A D; Rivera Aguilar, Víctor M; Lahr, Daniel J G; Hernández Moreno, Mayra M; Cuellar, Humberto Macías; Eguiarte, Luis E; Lara, Enrique (European journal of protistology, 2017)
Quadrulella (Amoebozoa, Arcellinida, Hyalospheniidae) is a genus of testate amoebae with unmistakable morphology, which secretes characteristic square plates to reinforce the test. They are mainly known from fens and freshwater habitats and have never been documented in deserts. We describe a new species, Quadrulella texcalense, from biological soil crusts in the intertropical desert of Tehuacán (state of Puebla, Mexico). Quadrulella texcalense occurred only at altitudes between 2140 and 2221m.a.s.l., together with the bryophyte genera Pseudocrossidium, Weissia, Bryum, Didymodon, Neohyophyla and Aloina. The soil was extremely dry (moisture of 1.97-2.6%), which contrasts sharply with previous reports for the Quadrulella genus. Single cell mitochondrial cytochrome oxidase I (COI) barcoding of thirteen isolated cells showed an important morphological variability despite having all the same COI barcode sequence. Quadrulella texcalense was placed in a tree containing other Hyalsopheniidae, including a newly barcoded South African species, Q. elegans. Q. texcalense unambiguously branched within genus Quadrulella in a compact clade but with a long branch, suggesting accelerated evolution due to a transition towards a new environment and/or under-sampling.
Keywords: druhová specificita; Mexiko; Phylogeny; Desert Climate; respirační komplex IV; pouštní klima; půda; fylogeneze; Electron Transport Complex IV; Soil; Species Specificity; Lobosea; Mexico